(untitled) (Journal of Applied Membrane Science & Technology, 2021)
In the present study, the effect of Sintering temperature, Particle size and Heating rate of the ceramic support membrane Elaboration based on dry clay were evaluated using full factorial design and investigated by porosity and mechanical strength measures. The flat supports have been prepared from 5 g of the material with a two fraction 2 and 30 µm, the extrusion was performed using the uniaxial pressing in applicant a pressure of 12 tones, the supports sintered between 900° C and 1200°C with a different heating rate (1°C/min and 10°C/min). By using full factorial design 23, it was found that the sintering temperature is the main controlling factors of the physical properties of dry ceramic support membrane, and its increase had a positive effect on Mechanical strength and negative effect on porosity. The interactions between the factors were relatively less important, and they had different (antagonistic/synergetic) influence on the properties. The optimal factors to elaborate the support membrane include a particle size of 2 µm, sintering temperature of 950°C, Heating rate of 1°C predicting the porosity of 40, 8% and Mechanical strength of 12 MPa.